Aerobic intramolecular carbon–hydrogen bond oxidation promoted by Cu(i) complexes. Issue 41 (15th October 2020) - Álvarez, María; Molina, Francisco; Fructos, Manuel R.; Urbano, Juan; Álvarez, Eleuterio; Sodupe, Mariona; Lledós, Agustí; Pérez, Pedro J.
Abstract : The complex TpMsCu(THF) undergoes the intramolecular oxidation of an alkylic C–H bond with O2, leading to the formation of a trinuclear compound where alkoxy and hydroxyl ligands are bonded to the copper centres. Abstract : The oxidation of C–H bonds by copper centres in enzymes with molecular oxygen takes place in nature under ambient conditions. Herein we report a similar transformation in which under ambient pressure and temperature (1 atm, 25 °C) the complex Tp Ms Cu(THF) (Tp Ms = hydrotris(3-mesityl-pyrazol-1-yl)borate) undergoes the intramolecular oxidation of an alkylic C–H bond with O2, leading to the formation of a trinuclear compound where alkoxy and hydroxyl ligands are bonded to the copper centres, as inferred from X-ray studies. The presence of adventitious Cu(0) derived from the partial decomposition of initial Tp Ms Cu(THF) facilitates the formation of such a trinuclear compound. DFT studies support the reaction taking place through a Cu(iii ) alkoxy-hydroxyl copper intermediate.